2020
DOI: 10.2147/ijn.s234679
|View full text |Cite
|
Sign up to set email alerts
|

<p>Enhanced and Prolonged Antitumor Effect of Salinomycin-Loaded Gelatinase-Responsive Nanoparticles via Targeted Drug Delivery and Inhibition of Cervical Cancer Stem Cells</p>

Abstract: Background: Cervical cancer stem cells (CCSCs) represent a subpopulation of tumor cells that possess self-renewal capacity and numerous intrinsic mechanisms of resistance to conventional chemotherapy and radiotherapy. These cells play a crucial role in relapse and metastasis of cervical cancer. Therefore, eradication of CCSCs is the primary objective in cervical cancer therapy. Salinomycin (Sal) is an agent used for the elimination of cancer stem cells (CSCs); however, the occurrence of several side effects hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…However, Sali is distributed in other organs such as liver, spleen, kidneys to various extents [ 42 , 48 , 49 ]. It has been reported that a dose of 2 mg/kg Sali induces significant changes and inflammatory cell infiltration in lung, heart muscle, liver, and spleen in mice [ 51 ]. Moreover, doses of 8–10 mg/kg Sali in free form have been proven lethal to mice [ 51 , 52 ].…”
Section: Salinomycin (Sali)mentioning
confidence: 99%
See 3 more Smart Citations
“…However, Sali is distributed in other organs such as liver, spleen, kidneys to various extents [ 42 , 48 , 49 ]. It has been reported that a dose of 2 mg/kg Sali induces significant changes and inflammatory cell infiltration in lung, heart muscle, liver, and spleen in mice [ 51 ]. Moreover, doses of 8–10 mg/kg Sali in free form have been proven lethal to mice [ 51 , 52 ].…”
Section: Salinomycin (Sali)mentioning
confidence: 99%
“…It has been reported that a dose of 2 mg/kg Sali induces significant changes and inflammatory cell infiltration in lung, heart muscle, liver, and spleen in mice [ 51 ]. Moreover, doses of 8–10 mg/kg Sali in free form have been proven lethal to mice [ 51 , 52 ]. Thus, incorporation of Sali in nanoparticles can reduce its side effects.…”
Section: Salinomycin (Sali)mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, nanoparticles have been widely studied as a drug delivery system because of their unique characteristics. 15 , 41 HDL has unique physicochemical properties, including naturally synthesized physiological components, amphiphilic apolipoproteins, specific protein–protein interactions, hydrophobic agent-incorporating and small size. 18 It has been proved that the phospholipid core of HDL can be combined with hydrophobic drugs to improve the water solubility of drugs and promote the effective release of drugs.…”
Section: Discussionmentioning
confidence: 99%